2000
DOI: 10.1038/sj.ijo.0801432
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of overweight tracking from childhood to adolescence: a 5 y follow-up study of Hat Yai schoolchildren

Abstract: OBJECTIVE: To study the determinants of overweight tracking from childhood to adolescence of Hat Yai schoolchildren. DESIGN: A longitudinal study. SETTING: Primary and secondary schools of Hat Yai municipality, southern Thailand. SUBJECTS: 2252 schoolchildren recruited in 1992 and follow-up for 5 y. MEASUREMENTS: Child's annual body mass index (BMI, kgam 2 ) from 1992 to 1997; parental BMIs, parental income, and family history of diseases by a questionnaire completed by parents in 1992. RESULTS: Prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…There is no evidence suggesting that the population's living standards have declined during this period (CNBS, 1999). In addition, although a large body of literature shows that, in general, about one-third of obese children and one-half of adolescents in the USA and many other industrialized countries remained obese as adults (Power et al, 1997;Serdula et al, 1993), using the IOTF and WHO overweight references, we and Mo-suwan et al found that only approximately 10% of overweight children remained overweight as adolescents 5 - International references for child and adolescent obesity Y Wang and JQ Wang 6 y later (Mo-suwan et al, 2000;Wang et al, 2000a,b). We suspect that at least part of the remarked difference is due to a lower sensitivity of these two references to identify overweight individuals during adolescence than childhood in developing countries.…”
Section: Discussionmentioning
confidence: 76%
“…There is no evidence suggesting that the population's living standards have declined during this period (CNBS, 1999). In addition, although a large body of literature shows that, in general, about one-third of obese children and one-half of adolescents in the USA and many other industrialized countries remained obese as adults (Power et al, 1997;Serdula et al, 1993), using the IOTF and WHO overweight references, we and Mo-suwan et al found that only approximately 10% of overweight children remained overweight as adolescents 5 - International references for child and adolescent obesity Y Wang and JQ Wang 6 y later (Mo-suwan et al, 2000;Wang et al, 2000a,b). We suspect that at least part of the remarked difference is due to a lower sensitivity of these two references to identify overweight individuals during adolescence than childhood in developing countries.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, obesity was more prevalent for those children when both parents were overweight compared with those with only one or neither parent was overweight (Mo-suwan, Tongkumchum, & Puetpaiboon, 2000). This could be due to sharing genes and unhealthy dietary habits of obese subjects and their obese parents.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence on the proportion of children whose overweight or obesity resolves is considerably more limited, and studies provide conflicting results 13 -15 . Various definitions of overweight resolution, small sample sizes 13 , poor retention rates 13,14 and different populations make the comparison of results across studies difficult. Yet these children are of particular interest, as they may offer insights into prevention and management strategies.…”
mentioning
confidence: 99%
“…For children in the middle childhood years the incidence of overweight and obesity appears to be relatively low 13,14 . However, the accuracy of these estimates is uncertain as the studies upon which these data are based had very low retention rates.…”
mentioning
confidence: 99%